Mechanical properties of square-steel confined-concrete quantitative pressure-relief arch and its application in a deep mine. Issue 1 (2nd January 2017) - Wang, Q.; Jiang, B.; Shao, X.; Wang, F.Q.; Li, S.C.; Guo, N.B.; Wang, B.Q.; Xiao, G.Q.; Pan, R.
Abstract: Providing support in deep and complex roadways is one of the major challenges in the mining industry; thus, a square-steel confined-concrete (SQCC) support system has been proposed and an SQCC quantitative pressure-relief arch (SQCC arch) has been developed for roadways in complex environments that are subject to high stress or are affected by faults or mining operations. A self-developed full-size large-scale test system for underground confined-concrete arches has been used to perform indoor comparative tests on a vertical-wall semicircle SQCC arch vs. a U29 arch, which is commonly used in mining. A combination of an indoor test and numerical analyses has shown that the SQCC arch deformation and failure pattern is 'bulged arch top, retracted arch leg'. The most severe damage position occurs in the area between the middle of the arch leg and the spandrel, and the quantitative pressure-relief device can be used effectively. Compared with the U29 arch's 'Z'-shaped bending failure pattern at the arch leg, overall out-of-plane instability and rapid decline in bearing capability, the SQCC arch's ultimate bearing capability is 2.15 times that of the U29 arch. In addition, the SQCC arch has an excellent bearing capability in the late stage. The SQCC arch support system is implemented in the fault-affected Zhaolou coal mine roadway to reinforce control over the surrounding rock. After 157 d, the maximum deformation at the arch measurement point is 33.1 mm, and the surrounding rock deformation is well controlled.